PENGARUH MEDIA PEMBELAJARAN ARTICULATE STORYLINE TERHADAP HASIL BELAJAR MATEMATIKA KELAS V SEKOLAH DASAR - Rahayu Soraya; Sinta Widya Ningtias (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
This study aims to determine the effect of articulate storyline learning media in learning outcomes of mathematics at grade V elementary school. The type of research was quantitative research. This research was conducted at SD Negeri 3 Rejosari in the second semester 2022/2023. The population of this study were all students of grade V consisted of VA and VB classes with a total of 44 students. The samples taken in this study were all V grade students with a total 44 students. Used sampling saturated sampling technique. The research method used in this research was Pre-Experimental Designs research, because there were no variables control. The form of the Pre-Experimental Design used by the researcher was the One-Group Pretest-Posttest Design, so in this design there was a pretest and a posttest. The data collection technique used in this study were test techniques and interview sheets. The test in this study was multiple-choice test consisting of 20 questions. Based on the results hypothesis testing paired sample t test shows that tcount < ttable, is 19,566 <2,021 with a Sig. (2-tailed) 0.000 < 0.05. Thus, it can be concluded that there was an effect of articulate storyline learning media in learning outcomes of mathematics at grade V elementary school.